------------------------------------
Find 10 reams
------------------------------------
1 ream = 32 ounces
10 reams = 32 x 10
10 reams = 320 ounces
------------------------------------
Convert ounce to pound:
------------------------------------
1 ounce = 0.0625
10 ounces = 0.0625 x 10
10 ounces = 0.625 pounds
------------------------------------------------------------------------
Answer: Each case weighs 0.625 pound.
------------------------------------------------------------------------
Lester-17
Jill-17+3=20
Together 17+20=37 inches.
Answer:
(x-4)(x+5)
Step-by-step explanation:
Find 2 numbers knowing sum (1) and product (-20). To find them, factor pairs of (-20) --> (-2,10) (-4,5). This sum is 1=b. Then, these 2 numbers are: - 4 and 5. Y=(x-4) (x+5). Hope this helped :)
![{ \qquad\qquad\huge\underline{{\sf Answer}}}](https://tex.z-dn.net/?f=%7B%20%5Cqquad%5Cqquad%5Chuge%5Cunderline%7B%7B%5Csf%20Answer%7D%7D%7D%20)
Here we go ~
In the above question, it is given that :
![\qquad \sf \boxed{ \sf f(x) = \frac{x + 3}{2} }](https://tex.z-dn.net/?f=%5Cqquad%20%5Csf%20%20%5Cboxed%7B%20%5Csf%20f%28x%29%20%3D%20%20%5Cfrac%7Bx%20%2B%203%7D%7B2%7D%20%7D)
A.) Find f(2) :
![\qquad \sf \dashrightarrow \: f(2) = \dfrac{2 + 3}{2}](https://tex.z-dn.net/?f=%5Cqquad%20%5Csf%20%20%5Cdashrightarrow%20%5C%3A%20f%282%29%20%3D%20%20%5Cdfrac%7B2%20%2B%203%7D%7B2%7D%20)
![\qquad \sf \dashrightarrow \: f(2) = \dfrac{5}{2}](https://tex.z-dn.net/?f=%5Cqquad%20%5Csf%20%20%5Cdashrightarrow%20%5C%3A%20f%282%29%20%3D%20%20%5Cdfrac%7B5%7D%7B2%7D%20)
or
![\qquad \sf \dashrightarrow \: f(2) = 0.5](https://tex.z-dn.net/?f=%5Cqquad%20%5Csf%20%20%5Cdashrightarrow%20%5C%3A%20f%282%29%20%3D%200.5)
B.) Find
:
![\qquad \sf \dashrightarrow \: let \: y = f (x)](https://tex.z-dn.net/?f=%5Cqquad%20%5Csf%20%20%5Cdashrightarrow%20%5C%3A%20let%20%5C%3A%20y%20%3D%20f%20%28x%29%20)
so, we can write it as :
![\qquad \sf \dashrightarrow \: y = \dfrac{x + 3}{2}](https://tex.z-dn.net/?f=%5Cqquad%20%5Csf%20%20%5Cdashrightarrow%20%5C%3A%20y%20%3D%20%20%5Cdfrac%7Bx%20%2B%203%7D%7B2%7D%20)
![\qquad \sf \dashrightarrow \: 2y = x + 3](https://tex.z-dn.net/?f=%5Cqquad%20%5Csf%20%20%5Cdashrightarrow%20%5C%3A%202y%20%3D%20x%20%2B%203)
![\qquad \sf \dashrightarrow \: x = 2y - 3](https://tex.z-dn.net/?f=%5Cqquad%20%5Csf%20%20%5Cdashrightarrow%20%5C%3A%20x%20%3D%202y%20-%203)
Now, put x =
, and y = x and we will get our required inverse function ~
![\qquad \sf \dashrightarrow \: f {}^{ - 1}(x) = 2x- 3](https://tex.z-dn.net/?f=%5Cqquad%20%5Csf%20%20%5Cdashrightarrow%20%5C%3A%20f%20%7B%7D%5E%7B%20-%201%7D%28x%29%20%3D%202x-%203)
C.) Find
:
![\qquad \sf \dashrightarrow \: f {}^{ - 1}(12) = 2(12)- 3](https://tex.z-dn.net/?f=%5Cqquad%20%5Csf%20%20%5Cdashrightarrow%20%5C%3A%20f%20%7B%7D%5E%7B%20-%201%7D%2812%29%20%3D%202%2812%29-%203)
![\qquad \sf \dashrightarrow \: f {}^{ - 1}(12) = 36- 3](https://tex.z-dn.net/?f=%5Cqquad%20%5Csf%20%20%5Cdashrightarrow%20%5C%3A%20f%20%7B%7D%5E%7B%20-%201%7D%2812%29%20%3D%2036-%203)
![\qquad \sf \dashrightarrow \: f {}^{ - 1}(12) = 33](https://tex.z-dn.net/?f=%5Cqquad%20%5Csf%20%20%5Cdashrightarrow%20%5C%3A%20f%20%7B%7D%5E%7B%20-%201%7D%2812%29%20%3D%2033)
And what happened?
you didn’t finish your sentence, lol